Factores que influyen en la deserción escolar en estudiantes del nivel primario en instituciones educativas de Iquitos 2025 - Linares Navarro, Mario Sander (2025)
The main purpose of this research was to analyze how economic, social, and educational factors affect school dropout among primary school students in public educational institutions in the district of Iquitos in 2025. The study was conducted within a quantitative approach, employing a correlational–causal, non experimental, and cross-sectional design. The sample consisted of 165 students, of whom 116 were selected through proportional stratified random sampling. To collect data, two questionnaires were applied: one to assess economic, social, and educational factors, and another to measure school dropout. Descriptive results showed that 46% of the students had a medium level of school dropout, 29% a low level, and 25% a high level. In the inferential analysis, the Spearman correlation test revealed that economic factors (ρ = 0,353; p < 0,001) and social factors (ρ = 0,336; p < 0,001) had a significant impact on school dropout, while educational factors did not show a statistically significant relationship (ρ = 0,.242; p < 0,001). Furthermore, the multiple linear regression model explained only 8,5% of the variability in school dropout (R² = 0,085), suggesting that other factors not considered in this study also influence dropout. In conclusion, school dropout at the primary level in Iquitos was at a medium level and was related to unfavorable economic and social conditions, highlighting the need to implement comprehensive public policies to address these issues.